Analysis of International Mobile Roaming Services with Smart Call Assistant System in GSM Originating Call - Elisabeth, Mareta; Sudiarta, Pande Ketut; Djuni, IGAK Diafari (Journal of Electrical, Electronics and Informatics, 2019)
In this research, it takes a trace log data with real testing using the Polystar and TrafficNews to know the comparison operator Telkomsel network calls with and without the SCA, as well as performance data call in roaming of Roamware SCA tools to know the Key Performance Indicator (KPI) from the parameters of the Call Setup Success Rate (CSSR) and Call Drop Rate (CDR) then be processed and analyzed to find out the quality of service the influence of SCA implementation calls the overall international operators in the three countries with the highest incoming data so that it could become the next parameter in the repair services provided. Results of the study to the difference between the signals operators are implemented with the SCA system of the inbound roaming customers. CSSR percentage in average in 3 countries, Australia, China, Singapore prior to SCA system in May of 81.48%, while after system restored by SCA of 90.98%, where after the repaired system SCA standard KPIS PT. Telkomsel i.e. normal state – good, whereas the percentage KPI failure calls (CDR) in 3 countries, Australia, China, Singapore prior to SCA system in May of 18.52%, while after the repaired system SCA amounted to 9.02%, where after improved system SCA standard KPI applied PT. Telkomsel into normal state.